Heavy Metals Evaluated in Some Well-Water Obtained from Almajiri Schools in Sokoto East, Nigeria - Yusuf Sarkingobir (Universitas Pendidikan Indonesia, 2023)
Heavy metals in water are due to pollution and are nowadays threat. The standard methods were utilized (including the atomic absorption spectroscopy) to determine the levels of Fe, Ni, Mn, Cr, Pb, and Cd in water collected from Almajiri schools in sokoto East, Nigeria. The levels of iron, nickel, and manganese in well water in Almajiri schools in Sokoto East, Nigeria. The ranges of the metals determined for iron, nickel, and manganese are respectively as follows: 3.110± 0.001- 3.100± 0.001 mg/dm3, 0.051± 0.001-0.662± 0.001 mg/dm3, and 0.001± 0.0001-0.021±0.001 mg/dm3 respectively. The highest element found was the iron, then nickel, and lastly manganese. The lead, chromium, and cadmium ranges are as follows: 0.005± 0.0002-0.06± 0.005 mg/dm3, 0.101± 0.001-0.231± 0.003 mg/dm3, and 0.0072± 0.0001-0.0213±0.001 mg/dm3 respectively; therein, the higher element evaluated was chromium, then cadmium, and lastly lead. Evaluated Pb, Cr, and Cd were higher than the WHO limits. It was found that, the levels of metals (Fe, Mn, Ni, Cr, Pb, and Cd) were elevated and could pose great risk to the children consumers by causing detrimental effects to health (including the nervous system defects) and poor academic performances.